Transatrial balloon atrial septostomy to facilitate weaning off venoarterial ECMO after pulmonary endarterectomy. Issue 10 (October 2022) - Ak, Koray; Arslanhan, Gökhan; Tire, Yakup; Tosun, Sinan; Kararmaz, Alper; Hanta, İsmail; Yıldızeli, Bedrettin
Atrial septostomy has been the last resort in the management of patients with the right ventricular failure related to pulmonary hypertension before lung transplantation. In this paper, we present a simple and safe technique (transatrial approach) for balloon atrial septostomy in a patient who required central venoarterial extracorporeal membrane oxygenation after pulmonary endarterectomy.